REVIEW ARTICLE: ULTRASOUND-GUIDED REGIONAL ANESTHESIA TECHNIQUES FOR POST-STERNOTOMY PAIN MANAGEMENT IN CARDIAC SURGERY - Ahmed Fathy Abdel-Latif Hasan, Mohammed Aly Mubarak Aly, Gad Sayed Gad, Abady Abdellah Ahmed (Chelonian Research Foundation, 2025)
Median sternotomy, a standard approach in cardiac surgery, is associated with significant postoperative pain that impacts recovery and patient satisfaction. Ultrasound-guided regional anesthesia techniques, such as the erector spinae plane block (ESPB) combined with superficial parasternal intercostal plane block (S-PIP) and the paravertebral block (PVB), have emerged as effective components of multimodal analgesia. These techniques reduce opioid reliance, mitigate adverse effects, and support enhanced recovery protocols. The review highlights their clinical utility, technical considerations, and potential for improving postoperative outcomes in cardiac surgery.